DAXX mediates high phosphate-induced endothelial cell apoptosis in vitro through activating ERK signaling - Wang,Shu; Wu,Mingyu; Qin,Ling; Song,Yaxiang; Peng,Ai (PeerJ, 2020)
Backgroud and Purpose Hyperphosphatemia, which is a high inorganic phosphate (Pi) level in the serum, promotes endothelial cells dysfunction and is associated with cardiovascular diseases in patients with chronic kidney diseases (CKD). However, the underlying mechanism of high Pi-induced endothelia cell apoptosis remains unclear. Methods Human umbilical vein endothelial cells (HUVECs) were treated with normal Pi (1.0 mM) and high Pi (3.0 mM), and then cell apoptosis, abnormal gene expression and potential signaling pathway involvement in simulated hyperphosphatemia were examined using flow cytometry, quantitative PCR (qPCR) and western blot analysis. A two-step 5/6 nephrectomy was carried out to induce CKD and biochemical measurements were taken. Results The rat model of CKD revealed that hyperphosphatemia is correlated with an increased death-domain associated protein (DAXX) expression in endothelial cells. In vitro, high Pi increased the mRNA and protein expression level of DAXX in HUVECs, effects that were reversed by additional phosphonoformic acid treatment. Functionally, high Pi resulted in a significantly increased apoptosis in HUVECs, whereas DAXX knockdown markedly repressed high Pi-induced cell apoptosis, indicating that DAXX mediated high Pi-induced endothelial cell apoptosis. High Pi treatment and DAXX overexpression induced the activation of extracellular regulated protein kinases (ERKs), while DAXX knockdown inhibited high Pi-induced ERKs activation. Finally, we demonstrated that DAXX overexpression induced HUVECs apoptosis in the presence of normal Pi, whereas additional treatment with U0126 (a specific ERK inhibitor) reversed that effect. Conclusion Upregulated DAXX promoted high Pi-induced HUVECs apoptosis by activating ERK signaling and indicated that the DAXX/ERK signaling axis may be served as a potential target for CKD therapy.
Keywords: Hyperphosphatemia; Chronic kidney diseases; HUVECs; DAXX; ERK